ANALISIS PROYEKSI PERTUMBUHAN PENDUDUK, TIMBULAN SAMPAH DAN KEBUTUHAN FASILITAS PENGELOLAAN SAMPAH DI BUKITTINGGI KOTA WISATA PADA TAHUN 2024-2028 - Azatri, Vina; Saleh, Nurmeizon; Nelvidawati, Nelvidawati; Hartuti, Sri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The aim of this research is to determine and analyze estimates of population growth and waste generation in West Sumatra Province, especially Bukittinggi City from 2024 to 2028; identify the need for waste management facilities in Bukittinggi City; To understand waste management, data analyzed using the logarithmic method from 2019 to 2023 shows an average population growth of 0.4% per year. In 2019, the population of Bukittinggi City was 124,562 people, and the amount of daily waste generated was 113.43 m3/day. Meanwhile, the population of Bukittinggi City is estimated to increase in 2028, and the amount of waste produced will be 127.78 m3/day. Thus, it is estimated that by 2028 the number of garbage truck systems will be 16 units. Apart from that, the number of containers needed in 2028 is 22 containers. There are several strategies to improve the quality and quantity of waste processing in Bukittinggi City, namely waste disposal must have adequate facilities and reliable management; Local governments must involve the community to develop a community mindset that prioritizes participation (increasing awareness and discipline) by introducing composting and Reuse, Reduce, Recycle (3R) systems as well as strengthening stakeholder collaboration.Keywords: waste, management, containers, truck, 3R.